(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
The emerging SARS-CoV-2 virus is an RNA virus that causes COVID-19 infection and corresponds to the Coronaviridae family. The newly sequenced virus appears to have originated in China and quickly spread all over the world, resulting in a pandemic that killed over 3,385,526 people until May 16th, 2021. As a result, researchers all over the world are working on an efficient vaccine to combat this disease, which will be critical in reducing morbidity and mortality. Covid-19 cases have been steadily increasing around the world due to a vaccine shortage. In collaboration with Dr Reddy’s Laboratories (DRL), Hyderabad Institute of Nuclear Medicine and Allied Sciences (INMAS), a lab of Defence Research and Development Organisation (DRDO) has developed 2-deoxy-D-glucose (2-DG) for the emergency use, as additive therapy for moderate to severe COVID-19 patients. The drug was found to be safe and improved the recovery of COVID-19 patients significantly. By Day 3, a large number of patients had progressed symptomatically and were no longer dependent on supplemental oxygen, suggesting early relief from Oxygen therapy or dependency.